What COVID-19 Means for Digital Infrastructure in Emerging Markets - Strusani, Davide (International Finance Corporation, Washington, DC, 2020)
The COVID-19 pandemic shows that digital connectivity is critical to societal resilience and business continuity in times of crisis. For digital infrastructure providers in emerging markets, higher demand for connectivity may be counterbalanced by a series of negative shocks. These could affect broadband operators and smaller companies, leading to less competition, limited availability of open-access broadband infrastructure, and reduced technological innovation. However, the perceived value of digital connectivity is likely to rise, creating opportunities to implement policy reforms to accelerate the rollout of 4G and 5G. Digital infrastructure companies, however, may accelerate their migration toward diversified business models. Against a background of funding withdrawal from emerging markets, financing for smaller or independent companies in the poorest economies may require substantial support from development finance institutions to preserve competition, improve resilience, and promote digital inclusion for the poorest.